Proceedings of the Twenty-Seventh Annual ACM-SIAM Symposium on Discrete Algorithms 2015
DOI: 10.1137/1.9781611974331.ch61
|View full text |Cite
|
Sign up to set email alerts
|

Better Distance Preservers and Additive Spanners

Abstract: We make improvements to the upper bounds on several popular types of distance preserving graph sketches. These sketches are all various restrictions of the additive pairwise spanner problem, in which one is given an undirected unweighted graph G, a set of node pairs P , and an error allowance +β, and one must construct a sparse subgraphThe first part of our paper concerns pairwise distance preservers, which make the restriction β = 0 (i.e. distances must be preserved exactly). Our main result here is an upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Perhaps surprisingly, Coppersmith and Elkin showed that nontrivial linear size distance preservers do indeed exist: in any undirected graph, one can preserve any p = O(n 1/2 ) pairwise distances using a subgraph on just O(n) edges. This unexpected fact has found several interesting applications: for example, Elkin and Pettie [26] used it to build the first linear-size log n stretch path reporting distance oracle, Bodwin and Vassilevska W. [13] have used it to build the current most accurate additive spanner of linear size, Pettie [38] used them as an ingredient in state-of-the-art constructions for mixed spanners, and they were employed by Elkin, Filtser, and Neiman [24] to build terminal subgraph spanners.…”
Section: Historymentioning
confidence: 99%
See 4 more Smart Citations
“…Perhaps surprisingly, Coppersmith and Elkin showed that nontrivial linear size distance preservers do indeed exist: in any undirected graph, one can preserve any p = O(n 1/2 ) pairwise distances using a subgraph on just O(n) edges. This unexpected fact has found several interesting applications: for example, Elkin and Pettie [26] used it to build the first linear-size log n stretch path reporting distance oracle, Bodwin and Vassilevska W. [13] have used it to build the current most accurate additive spanner of linear size, Pettie [38] used them as an ingredient in state-of-the-art constructions for mixed spanners, and they were employed by Elkin, Filtser, and Neiman [24] to build terminal subgraph spanners.…”
Section: Historymentioning
confidence: 99%
“…Figure 1: State of the art upper and lower bounds for pairwise distance preservers, for directed/undirected and weighted/unweighted graphs. The first upper bound for undirected unweighted graphs is due to [13], and the remaining bounds in this chart are all due to [19]. The hidden n o(1) factor in the unweighted lower bound has the form 2…”
Section: Upper Bound Lower Boundmentioning
confidence: 99%
See 3 more Smart Citations